Low-fouling surface plasmon resonance biosensor for multi-step detection of foodborne bacterial pathogens in complex food samples - Vaisocherová-Lísalová, Hana; Víšová, Ivana; Ermini, Maria Laura; Špringer, Tomáš; Song, Xue Chadtová; Mrázek, Jan; Lamačová, Josefína; Scott Lynn, N; Šedivák, Petr; Homola, Jiří (Biosensors & bioelectronics, 2016)
Recent outbreaks of foodborne illnesses have shown that foodborne bacterial pathogens present a significant threat to public health, resulting in an increased need for technologies capable of fast and reliable screening of food commodities. The optimal method of pathogen detection in foods should: (i) be rapid, specific, and sensitive; (ii) require minimum sample preparation; and (iii) be robust and cost-effective, thus enabling use in the field. Here we report the use of a SPR biosensor based on ultra-low fouling and functionalizable poly(carboxybetaine acrylamide) (pCBAA) brushes for the rapid and sensitive detection of bacterial pathogens in crude food samples utilizing a three-step detection assay. We studied both the surface resistance to fouling and the functional capabilities of these brushes with respect to each step of the assay, namely: (I) incubation of the sensor with crude food samples, resulting in the capture of bacteria by antibodies immobilized to the pCBAA coating, (II) binding of secondary biotinylated antibody (Ab2) to previously captured bacteria, and (III) binding of streptavidin-coated gold nanoparticles to the biotinylated Ab2 in order to enhance the sensor response. We also investigated the effects of the brush thickness on the biorecognition capabilities of the gold-grafted functionalized pCBAA coatings. We demonstrate that pCBAA-compared to standard low-fouling OEG-based alkanethiolate self-assemabled monolayers-exhibits superior surface resistance regarding both fouling from complex food samples as well as the non-specific binding of S-AuNPs. We further demonstrate that a SPR biosensor based on a pCBAA brush with a thickness as low as 20 nm was capable of detecting E. coli O157:H7 and Salmonella sp. in complex hamburger and cucumber samples with extraordinary sensitivity and specificity. The limits of detection for the two bacteria in cucumber and hamburger extracts were determined to be 57 CFU/mL and 17 CFU/mL for E. coli and 7.4 × 10(3) CFU/mL and 11.7 × 10(3)CFU/mL for Salmonella sp., respectively. In addition, we demonstrate the simultaneous detection of E. coli and Salmonella sp. in hamburger sample using a multichannel SPR biosensor having appropriate functional coatings.
Keywords: Limit of Detection; Food safety; Detection of bacterial pathogens; limita detekce; potravinářská mikrobiologie; Humans; zlato; povrchová plasmonová rezonance; Biosensing Techniques; imobilizační protilátky; Polymer brushes; lidé; biosenzitivní techniky; Food Microbiology; Escherichia coli O157; Low-fouling biorecognition coatings; Surface Plasmon Resonance; kontaminace potravin; Food Contamination; nemoci přenášené potravou; Gold nanoparticles; Antibodies, Immobilized; Gold; E. coli O157:H7; Surface plasmon resonance biosensor; Foodborne Diseases